A case of nonislet cell tumor hypoglycemia associated with malignant mesothelioma requiring a multifaceted approach for optimal glycemic control. Issue 10 (28th October 2021) - Ono, Mariko; Maeda, Yuki; Koyama, Nobuyuki; Nagase, Terumasa; Katsura, Yoshiya; Nakamura, Hiroyuki; Aoshiba, Kazutetsu
Abstract: Nonislet tumor hypoglycemia (NICTH) is a rare paraneoplastic syndrome characterized by refractory hypoglycemia, which often requires multifaceted therapy. We reported a case of a patient with pleural malignant mesothelioma and developed NICTH, for which chemotherapy, glucocorticoids, and nutrition were given to achieve optimal glycemic control. Abstract : In patients with tumors and hypoglycemia without clear etiology, nonislet cell tumor hypoglycemia (NICTH), which can cause severe refractory hypoglycemia, should be considered. If tumor resection is not feasible, a multifaceted therapeutic approach that includes anticancer drugs, corticosteroids, and nutrition may be required for the management of NICTH.